2007
DOI: 10.1111/j.1440-1746.2007.05112.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of 904 patients with hepatocellular carcinoma in a hepatitis B virus–endemic area

Abstract: The results of this study will be helpful in determining the survival outcomes and treatment strategies for HCC patients in HBV-endemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
101
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 29 publications
(63 reference statements)
6
101
1
Order By: Relevance
“…PVTT can also decrease portal flow that may lead to ascites, jaundice, hepatic encephalopathy, or liver failure. Therefore, the presence of PVTT is one of the most significant prognostic factors of poor prognosis [21,22] , and it has been reported that these patients survive only 2.7-4 mo if left untreated [22,23] . In advanced HCC patients with PVTT, standard treatments have not been established, especially in the Asia-Pacific region.…”
Section: Discussionmentioning
confidence: 99%
“…PVTT can also decrease portal flow that may lead to ascites, jaundice, hepatic encephalopathy, or liver failure. Therefore, the presence of PVTT is one of the most significant prognostic factors of poor prognosis [21,22] , and it has been reported that these patients survive only 2.7-4 mo if left untreated [22,23] . In advanced HCC patients with PVTT, standard treatments have not been established, especially in the Asia-Pacific region.…”
Section: Discussionmentioning
confidence: 99%
“…Serum a-fetoprotein level and tumor stage (by the modified UICC and the BCLC systems) affected uptake only of 18 F-FDG. For analyzing accuracy in the detection of small tumors or extrahepatic metastases, we prospectively enrolled more patients who had modified UICC stage I, II, and IVb, compared with the patient population of our previous report (27). A high rate of positive findings on 18 F-FDG PET has been reported in patients with elevated serum a-fetoprotein levels (7) and in patients with poorly differentiated HCC (28).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic options are stage-dependent (6,7). Only approximately 30% of patients who present with early stage tumors undergo resection, liver transplantation and percutaneous ablation, due to various factors, such as multifocal tumor and poor liver function resulting from underlying cirrhosis (8)(9)(10). Until recently, no effective treatment was available for these conditions (11).…”
Section: Introductionmentioning
confidence: 99%